Growth and characterization studies of rosaniline dye with KDP single crystal for optoelectronic applications. (2021) - Manivannan, V.; Bhadhusha, N.; Rajapriya, R.; Gunasekaren, T.; Uthrakumar, R.; Kaviyarasu, K.
Abstract: Good quality of single crystal of pure and fusion with Potassium Di hydrogen Ortho Phosphate (KDP) has been successfully grown form aqueous solution by slow cooling evaporating technique. The grown crystal characterized by FTIR, UV-visible spectral Analysis. Therefore, X-ray diffraction data reveals crystalline perfection the improved transparency for the doped crystal ascertain the inclusion of metal ion in the lattice. However, the photoluminescence studies indicate that the grown crystals have a green fluorescence emission. Dielectric studies have been carried out for the grown crystal and the results were discussed in detail.